Investigation of supercritical CO2 mass transfer in porous media using X-ray micro-computed tomography. (January 2023) - Huang, Ruotong; Herring, Anna L.; Sheppard, Adrian
Abstract: Understanding the mass transfer of CO 2 into formation brine both qualitatively and quantitatively is important for improving the security of geologic carbon sequestration. In this study, quasi-dynamic X-ray micro-computed tomographic (MCT) imaging was used to track the time-evolution of supercritical CO 2 (scCO 2 ) clusters in a sandstone throughout brine injection. A cluster-matching workflow enabled the identification of depletion, merging, and snap-off of the scCO 2 clusters, and subsequently the mass transfer coefficient of individual scCO 2 clusters was found to range between 3.0 × 10 − 5 and 3.5 × 10 − 4 mm/s. The macroscopic average mass transfer coefficient was estimated as 1.4 × 10 − 4 mm/s. For application to geologic carbon sequestration, these values give an indication of the range of mass transfer coefficients that may be expected for similar state and flow conditions. With the macroscopic average mass transfer coefficient evaluated, we back-calculated the in-situ CO 2 concentration field for brine, which provides quantitative insight of the distribution of dissolved CO 2 in the sample. Despite slow injection rate (Ca = 10 − 7 ), mobilization of small scCO 2 clusters was also observed, and was attributed to the combined effect of incomplete dissolution of snapped-off clusters and the reduction in the fluid–fluid interfacial tension (IFT) due to the high local CO 2 concentration in brine accompanying scCO 2 dissolution. This highlights the coupling of dissolution and mobilization processes and demonstrates the need to understand these interlinked dynamics to improve CO 2 storage in geological formations. Highlights: Experiment of scCO2 clusters dissolution into brine imaged with microtomography. Time-evolution of scCO2 clusters tracked via a cluster-matching workflow. Mass transfer coefficient for individual scCO2 clusters and the system are evaluated. Method of back-calculation of the CO2 concentration field in brine is proposed. Results demonstrate coupling of scCO2 dissolution and displacement.